The Implementation Of Rewards And Punishments Towards Students Motivation In English Learning - L, Syahrir; hermansyah, Sam; Nadirah, Nadirah; Rasyid, Rustam efendy; Buhari, Buhari; Sartika, Sartika (La Ogi : English Language Journal, 2023)
This research uses descriptive qualitative research as a research methodology located at SMP Negeri 3 Pitu Riase. This research was conducted to determine the implementation process of giving rewards and punishments to increase students' learning motivation and to find out the results of the implementation of giving rewards and encouragement to increase students' learning motivation in English subjects. Data collection techniques used are observation, interviews and documentation. While data analysis used data reduction, data presentation and data verification. The data obtained from this study is divided into two, namely data in the form of verbal (words) for example "Good" and nonverbal (actions) for example thumbs up, applause, additional points, advice, reprimand, vocabulary memorization, deductions and pinches. This data was obtained from the treatment and words of the teacher to his students during the learning process. The results of the research from the implementation of reward and punishment to increase students' motivation to learn in English subjects at SMP Negeri 3 Pitu Riase show that: the process of implementing reward and punishment is carried out spontaneously in the classroom and sometimes there is an agreement with students if there are students who violate or Failure to do the work will be punished. Rewards are given in the form of praise, applause, thumbs up and additional points. The punishment is in the form of advice, standing in front of the class and memorizing vocabulary. The results of the implementation of reward and punishment are: (1) The level of student attention to learning increases; (2) The level of student confidence in the ability to do learning tasks; (3) The level of student satisfaction with the learning process that has been carried out; and (4) Determining actions which must be done.